Livelihood transitions and the changing nature of farmer-herder conflict in Sahelian West Africa - Turner, M.D.; Ayantunde, Augustine A.; Patterson, K.P.; Patterson, E.D. (Informa UK Limited, 2011)
The accommodation of livestock husbandry with crop agriculture is crucial for the future of the West African Sahel. Present trends are leading to greater restrictions on livestock husbandry and a growing convergence of livelihood practices among groups whose identities are tied to herding and farming. Using the cases of four rural communities in Niger, this study adopts an 'access to resources' framework to analyse the causal connections among: rural peoples' livelihood strategies, everyday social relations of production, perceptions of social groups' identities, and the potential for farmer-herder conflict. While the convergence of livelihoods arguably increases the frequency of conflict triggers, it has also, through the expansion of shared common interests and cross-group, production-related relationships, improved the ability of communities to effectively manage these incipient conflicts.